Crypto Asset-Trade Resilience During The Covid-19 Pandemic In Indonesia - Vicko Taniady; Salsabiila Puteri Permatasari; Reyka Widia Nugraha (Jurnal Jurisprudence, 2021)
Purpose of the study: This research aims to examine the resilience, existence, and security of crypto assets in Indonesia. In fact, bitcoin's presence results in pros and cons in society, so there is a need for a deeper study of crypto assets. Methodology: The research method used was normative-empirical law using a statutory approach and case studies. This research also employed literature study techniques to reveal theory, data, etc. Results: The results of this study indicated that the sustainability of crypto-asset trading in Indonesia has increased in demand even during the pandemic, and the public can perform trading activities safely because there are already several legal umbrellas related to crypto asset trading in Indonesia, which are regulated by Bappebti (Commodity Futures Trading Supervisory Agency). Applications of this study: This research is expected to provide literature related to crypto-asset regulation in Indonesia. On the other hand, the authors hope that this paper will be able to provide public awareness in conducting crypto-asset transactions in the form of bitcoin. Novelty/ Originality of this study: To obtain government protection in conducting crypto asset trading, customers need to choose crypto asset traders who have been registered and comply with the rules set by Bappebti. With the emergence of high risk in trading, the authors expect the costumers to be careful when choosing crypto asset traders.